Management of Palpebra Rupture Cases in Children: A Case Report - Milenia Syawali; Oktarina Nila Juwita; Anissya Rima Oktavia (Jurnal Impresi Indonesia, 2025)
Eyelid injuries, particularly palpebral lacerations, are common in pediatric patients and require meticulous management to prevent long-term functional and cosmetic issues. These injuries, often resulting from trauma, pose significant challenges, as they involve both the skin and deeper structures of the eyelid. This case report discusses the management of a 7-year-11-month-old child who sustained a full-thickness eyelid laceration after falling and hitting a stone. The patient presented with sharp pain, difficulty in opening the eyelid, and bleeding. A physical examination revealed a full-thickness laceration on the superior margin of the left eyelid, with accompanying edema and subconjunctival hemorrhage. Imaging tests were not required as no orbital injury was suspected. The patient underwent eyelid reconstruction within 72 hours, and postoperative care included antibiotic treatment and wound management. The surgical outcome was successful, with optimal cosmetic and functional results. This case underscores the importance of timely and precise surgical intervention to minimize complications and achieve satisfactory results in pediatric palpebra injuries. Further research is needed to establish comprehensive guidelines for managing eyelid trauma in children, particularly regarding surgical techniques and postoperative care to ensure the best outcomes for young patients.